2006
DOI: 10.1007/s11089-006-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Clergy Role Stress and Satisfaction: Role Ambiguity Isn’t Always Bad

Abstract: This study examined relationships between role conflict and role ambiguity and clergy satisfaction with their church appointment. Questionnaire data obtained from 293 United Methodist clergy suggested that role conflict and role ambiguity each have a negative relationship with appointment satisfaction. However, when considered together, they displayed a more complex relationship with appointment satisfaction. Contrary to conventional wisdom, results indicated that although these stressors operate together to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
1
22
0
2
Order By: Relevance
“…This suggests that respondent who felt heavy demands made upon them are also less satisfied with their job. This findings is consistent with Kemery (2006), Correa andFerreira (2011), andRai (2013). Butt and Lance (2005) found that role overload was related to job satisfaction among secondary school teachers.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This suggests that respondent who felt heavy demands made upon them are also less satisfied with their job. This findings is consistent with Kemery (2006), Correa andFerreira (2011), andRai (2013). Butt and Lance (2005) found that role overload was related to job satisfaction among secondary school teachers.…”
Section: Discussionsupporting
confidence: 83%
“…In a study, Kemery (2006) found that, although role conflict and role ambiguity individually had negative relationships with job satisfaction, the combined effect of the two factors on appointment satisfaction was more complex. When role conflict and role ambiguity were both high, appointment satisfaction was low, but when role conflict was low, satisfaction was actually higher when role ambiguity was high.…”
Section: Link Between Occupational Stress and Job Satisfactionmentioning
confidence: 99%
“…Our set of arguments is not new for role stress research. In fact, arguments by Kemery (2006) recently found evidence for a double-edged sword phenomenon of role ambiguity, where both negative and positive effects could be expected. Moreover, Van Sell et al (1981) suggested role ambiguity facilitates role behavior at optimal levels of the former.…”
Section: Inverted U-shape Relationship Between Role Ambiguity and Selmentioning
confidence: 99%
“…Systemic dynamics such as boundary ambiguity, intrusiveness, and congregational idealization of the pastor, the pastor's spouse, and their children have been identified as potential contributors to distress among clergy and their families (e.g., Hill et al 2003;Lee 1999;Blanton 1998, 1994) as well as lower job satisfaction (Kay 2000;Kemery 2006). How clergy and their spouses work together to manage these potentially stressful dynamics could be pivotal in creating a context that fosters their own wellbeing and that of the congregation.…”
Section: Research On Clergy Stress and Copingmentioning
confidence: 99%
“…Clergy and clergy spouses who fail to establish clear rules, expectations, and/or boundaries with their congregations are more likely to experience increased congregational intrusiveness and stress (Morris and Blanton 1998;Boyar et al 2003;Kemery 2006;McMinn et al 2005). Lack of clear rules, procedures, or objectives for handling the demands of the pastorate can lead to confusion and less confidence in their right to refuse demands for their time and energy, undermining healthy boundaries and potentially increasing emotional exhaustion (Boyar et al 2003).…”
Section: Research On Clergy Stress and Copingmentioning
confidence: 99%